ANTIMICROBIAL, CYTOTOXIC AND HEMOLYTIC ACTIVITIES OF MARINE ALGAE-ASSOCIATED FUNGAL ISOLATES IN VIETNAM - Chi, Hoang Kim; Ha, Tran Thi Hong; Cuong, Le Huu; Hang, Tran Thi Nhu; Tuan, Nguyen Dinh; Nhung, Le Thi Hong; Huong, Le Mai (Vietnam Journal of Marine Science and Technology, 2019)
In the context of sources for natural products discovery are going scarcer, exploiting biotechnologically potential compounds from marine microbial symbionts is considered a relatively new trend. In our study a total of fifteen fungal strains were isolated from marine algal samples belonging to species Kappaphycus cottonii, K. striatus, Gracilaria eucheumatoides and Betaphycus gelatinus collected in Nha Trang in 2017. The in vitro biological activities, including antimicrobial, cytotoxic and hemolytic activities of ethyl acetate extracts of the fungal strains were determined. From fifteen fungal extracts, six displayed antimicrobial activity against at least one test strain. At 20 μg.ml-1, four fungal extracts were found to express cytotoxic activity on two human cancer cell lines hepatocellular carcinoma (Hep-G2) and breast adenocarcinoma (MCF-7), with G. eucheumatoides being the source of the highest number of producer strains. Hemolytic activity was observed in rabbit erythrocytes under almost all fungal extracts’ effect. No apparent relationship was observed between the biological activities of fungal isolates. The biological assessments uncovered several fungal candidates, such as Bge-1.1, Kco-2.1 and Geu-1.1 with relatively potent antimicrobial and cytotoxic activities while expressing less hemolytic effect at concentrations from 20 μg.ml-1 to 200 μg.ml-1. The results evidenced the potential of exploiting natural products from associated marine microorganisms, especially those for the purpose of pharmaceutical applications.